Detection of Quiescent Radioresistant Epithelial Progenitors in the Adult Thymus - Dumont-Lagacé, Maude; Gerbe, Hervé; Daouda, Tariq; Laverdure, Jean-Philippe; Brochu, Sylvie; Lemieux, Sébastien; Gagnon, Étienne; Perreault, Claude (Frontiers in Immunology, 2017)
Thymic aging precedes that of other organs and is initiated by the gradual loss of thymic epithelial cells (TECs). Based on in vitro culture and transplantation assays, recent studies have reported on the presence of thymic epithelial progenitor cells (TEPCs) in young adult mice. However, the physiological role and properties of TEPC populations reported to date remain unclear. Using an in vivo label-retention assay, we previously identified a population of quiescent but non-senescent TECs. The goals of the present study were therefore i) to evaluate the contribution of these quiescent TECs to thymic regeneration following irradiation-induced acute thymic injury, and ii) to characterize their phenotypic and molecular profiles using flow cytometry, immuno-histology and transcriptome sequencing. Based on label-retention and BrdU labeling assays, we now report that while UEA1+ TECs proliferate actively in steady-state conditions, they undergo proliferative arrest and cell loss following irradiation. On the opposite, the UEA1–quiescent TECs are radioresistant and proliferate in situ following acute thymic injury, thereby contributing to thymic regeneration in 28-30 week-old mice. Most UEA1– quiescent TECs display an undifferentiated phenotype (co-expression of K8 and K5 cytokeratins) and express high levels of genes that regulate stem cell activity in different tissues (e.g., Podxl, Ptprz1). Additionally, two features suggest that UEA1– quiescent TECs occupy discrete stromal niches: i) their preferential location in clusters adjacent to the cortico-medullary junction, and ii) their high expression of genes involved in crosstalk with mesenchymal cells. Together with their undifferentiated phenotype and their high expression of stemness-associated genes, the ability of UEA1– quiescent TECs to participate to TEC regeneration qualifies them as in vivo relevant TEPCs.